Structure of the putative long tail fiber receptor-binding tip of a novel temperate bacteriophage from the Antarctic bacterium Bizionia argentinensis JUB59 - Pellizza Pena, Leonardo Agustín; López, José L.; Vázquez, Susana Claudia; Sycz, Gabriela; Guimarães, Beatriz G.; Rinaldi, Jimena Julieta; Goldbaum, Fernando Alberto; Aran, Martin; Mac Cormack, Walter Patricio; Klinke, Sebastian (Journal of Structural Biology)
Tailed bacteriophages are one of the most widespread biological entities on Earth. Their singular structures, such as spikes or fibers are of special interest given their potential use in a wide range of biotechnological applications. In particular, the long fibers present at the termini of the T4 phage tail have been studied in detail and are important for host recognition and adsorption. Although significant progress has been made in elucidating structural mechanisms of model phages, the high-resolution structural description of the vast population of marine phages is still unexplored. In this context, we present here the crystal structure of C24, a putative receptor-binding tip-like protein from Bizionia argentinensis JUB59, a psychrotolerant bacterium isolated from the marine surface waters of Potter Cove, Antarctica. The structure resembles the receptor-binding tip from the bacteriophage T4 long tail fiber yet showing marked differences in its domain organization, size, sequence identity and metal binding nature. We confirmed the viral origin of C24 by induction experiments using mitomycin C. Our results reveal the presence of a novel uncharacterized prophage in the genome of B. argentinensis JUB59, whose morphology is compatible with the order Caudovirales and that carries the nucleotide sequence of C24 in its genome. This work provides valuable information to expand our current knowledge on the viral machinery prevalent in the oceans. Fil: Pellizza Pena, Leonardo Agustín. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Instituto de Investigaciones Bioquímicas de Buenos Aires. Fundación Instituto Leloir. Instituto de Investigaciones Bioquímicas de Buenos Aires; Argentina Fil: López, José L. Universidad de Buenos Aires. Facultad de Farmacia y Bioquimica. Instituto de Investigaciones En Bacteriologia y Virologia Molecular; Argentina Fil: Vázquez, Susana Claudia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de ...